KINERJA PEGAWAI UNIT KERJA LAYANAN (UKL) DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KABUPATEN PESISIR SELATAN - Azrina Putri; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
ABSTRAK The purpose of this study was to determine the performance of the Employment Service Unit (UKL) of the Population and Civil Registry Service in population administration services in the South Coastal District. This research is a qualitative research using descriptive method. The informant of this research was determined by the purpose sampling technique, accompanied by Kassubag. General and Civil Service Office of Population and Civil Registration, Kasi. Collaboration and Service Innovation in the Population and Civil Registration Service of Pesisir Selatan Regency, Head of Service Work Unit (UKL) of Bayang sub-district, IV Jurai sub-district and Koto XI Tarusan sub-district, as well as the people who take care of population administration. Data collection techniques were carried out by means of observations, interviews and documentation studies. To test the validity of the data used source triangulation techniques. The results showed that the performance of the Service Work Unit (UKL) employees in population administration services in the South Coastal District in practice was still poor, namely in aspects of ability and expertise, knowledge, work design, personality, and work environment. There are factors that affect the performance of the Service Work Unit (UKL) employees, as well as the efforts made to improve the performance of the Service Work Unit (UKL) employees. Keyword : employee performance, service, population administration